Identification of the Genomics and Transcriptomics Regulators of the DNA Damage Response in Breast Cancer - Mehdi Sadeghi; Mohammad Reza Karimi; Amir Hossein Karimi (Journal of Genetic Resources)
Breast cancer is one of the most prevalent malignancies and the most common cancer in female patients. In recent years, the clinical utilization of a class of drugs called poly (ADP-ribose) polymerase inhibitors has been observed to be detrimental to cells that harbor defective DNA damage repair mechanisms. Implementation of these drugs entails a series of unprecedented challenges, including the development of drug resistance to this treatment strategy. Thus, it is essential to gain a better understanding of the mechanisms that regulate the DNA damage response to maximize the treatment efficacy in breast cancer patients and minimize unwanted side effects. In this study, through the utilization of single-cell- and bulk-level transcriptional data, we set out to identify molecules and molecular circuits associated with DNA damage response in breast cancer patients. By identifying differentially expressed genes in single-cell cancer cell populations inherently different in DNA damage response, further clustering bulk RNA-sequencing samples based on the expression of these genes, and performing network and enrichment analysis at the bulk level, we have characterized breast cancer samples based on their DNA damage response. Moreover, we have been able to identify a central network module whose members can serve as treatment targets and yield further insights into the mechanisms of drug resistance and DNA damage response in breast cancer. Overall, this study contributes to the characterization of the transcriptional circuits involved in the heterogeneity of DDR in breast cancer and provides candidate avenues for the investigation of potential therapeutic interventions.